2010
DOI: 10.1590/s0102-05362010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e produção de gérbera fertirrigada com solução nutritiva

Abstract: Growth and production of gerbera fertigated with nutrient solutionThis work aimed to evaluate growth and production characteristics of four potted gerbera cultivars fertigated with two nutrient solutions. The experiment was carried out in a greenhouse from May to July 2006 at UNESP, Botucatu, São Paulo State, Brazil. Experimental design was in randomized blocks in a 4x2 factorial arrangement, with 4 gerbera cultivars (Cherry, Golden Yellow, Salmon Rose and Orange) and 2 nutrient solutions. The plants were cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 8 publications
(1 reference statement)
0
12
2
6
Order By: Relevance
“…Thus, considering these classification parameters, the gerbera plants of all treatments in the experiment had a quality standard for commercialization in class II. Ludwig et al (2010) found in potted gerbera cultivars fertigated with nutrient solutions that the shoot and inflorescence diameter ranged, respectively, from 31.4 to 35 cm, and from 8.8 to 9.3 cm, and that the plants had, on average, 2.8 inflorescences per pot. Guerrero et al (2013) obtained potted gerbera plants (cultivar Red) with 27.2 cm of mean shoot diameter, with 8.6 cm mean inflorescence diameter, and, on average, 2.9 inflorescences per pot, in an experiment using substrate and nutrient solution.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Thus, considering these classification parameters, the gerbera plants of all treatments in the experiment had a quality standard for commercialization in class II. Ludwig et al (2010) found in potted gerbera cultivars fertigated with nutrient solutions that the shoot and inflorescence diameter ranged, respectively, from 31.4 to 35 cm, and from 8.8 to 9.3 cm, and that the plants had, on average, 2.8 inflorescences per pot. Guerrero et al (2013) obtained potted gerbera plants (cultivar Red) with 27.2 cm of mean shoot diameter, with 8.6 cm mean inflorescence diameter, and, on average, 2.9 inflorescences per pot, in an experiment using substrate and nutrient solution.…”
Section: Resultsmentioning
confidence: 96%
“…72 days after transplanting, at the gerbera marketing time, defi ned according to Guerrero et al (2013), the following parameters were evaluated: largest shoot diameter of the plants, measured with the aid of a tape measure at two points perpendicular to the end of opposite leaves; number of stems; stem length; infl orescence diameter and stem weight, according to the procedures described in Ludwig et al (2010) and Muniz et al (2013). Subsequently, a fully expanded leaf was collected from each pot, according to Tombolato et al (1997); they were washed, dried in a forced air oven at about 60 °C, and milled to determine P contents in the leaf tissue (TEDESCO et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its expanding commercial production, research has not kept pace, with little information on cultivation, especially with regard to nutrition and fertilization (Ludwig et al, 2010a). As a result, fertilizers used by farmers are derived from companies' techniques empirical observations (Ludwig et al, 2010b;Muniz et al, 2013). Pesticide use has increased due to high pest incidence in culture (Cardoso and Silva, 2013).…”
Section: Introductionmentioning
confidence: 99%